Sistem Informasi Akademik SMA Negeri 1 Kintap Berbasis Web - Anwar, Choirul; Amalia, Anita (mijournal.org, 2023)
SMA Negeri 1 Kintap is one of the educational institutions located in Kintap District. Until now, there are still many educational institutions that have not implemented an academic information system, one of which is SMA Negeri 1 Kintap. Data management still uses processes that refer to documents in the form of files or archives, still uses Microsoft Excel and Microsoft Word applications, without a database. In addition, the principal is also difficult to put together academic reports. This study aims to build an academic information system to streamline time and make it easier for related parties to process and display. The method used in building this system is the waterfall method using the PHP and MySQL programming languages. This study uses data collection methods through literature study and interviews. The method used for testing or evaluation is the black box method. The black box method focuses on the function of a system. The result of this research is the web-based academic information system of SMA Negeri 1 Kintap.